A RETROSPECTIVE STUDY ON CERVICAL TUBERCULAR LYMPHADENOPATHY. - Sushil Pandey; Ashish Tirkey (Student's Journal of Health Research, 2023)
Background: India has the highest incidence of tuberculosis in the globe, with twenty percent of cases. In India, tuberculous lymphadenitis is the most prevalent extrapulmonary variant of tuberculosis. The purpose of this study is to share our knowledge regarding tuberculous cervical lymphadenitis. Methods: This hospital-based prospective investigation was conducted for one year in the Department of General Surgery at MRMCH, Daltonganj. All cases of neck edoema or cervical lymphadenitis selected for the study were initially treated conservatively with antibiotics and evaluated after two weeks. If the neck edoema persists, FNAC, USG, and occasionally a biopsy are performed. Results: Out of 120 study cases, infectious or inflammatory aetiology was observed in 47.5%, tuberculous lymphadenopathy in 33.333%, metastatic nodes in 13.335%, lymphoma in 1.67%, and non-specific lymphadenitis in 4.17 % of cases.  Analysis of 40 cases of tuberculous lymphadenopathy revealed that those between the ages of 15 and 24 were most frequently affected. 68% of the cases were female and 32% were male. Level V cervical lymph nodes were most commonly involved. Ultrasonography of tuberculous lymph nodes revealed hypoechogenicity and necrosis in all cases, matted lymph nodes in forty percent of cases, calcifications in twenty-seven percent of cases, and pointed margins in sixty-seven percent of cases. Tests for tuberculin were only positive in 73% of cases. Conclusion: In developing nations like India, there is a high prevalence of tuberculous cervical lymphadenitis among patients with enlarged neck lymph nodes. Adenopathy of the cervical lymph nodes is the most prevalent manifestation of the extrapulmonary form of tuberculosis. Therefore, it is essential that otolaryngologists are aware of tuberculosis in the head and neck region, which can aid in early diagnosis with the assistance of simple investigations, allowing patients to be promptly and effectively treated.